1992
DOI: 10.1002/ar.1092340406
|View full text |Cite
|
Sign up to set email alerts
|

Architectural design, fiber‐type composition, and innervation of the rat rectus abdominis muscle

Abstract: The rectus abdominis muscle is architecturally compartmentalized by tendinous intersections and is supplied by multiple thoracic nerves. In this study, the rectus abdominis of the rat has been qualitatively and quantitatively examined with regard to muscle dimensions, fiber organization, fiber-type composition, and innervation. The muscle exhibits architectural heterogeneity and different patterns of innervation among its thoracic, epigastric, and hypogastric parts. The epigastric part, adherent to the rectus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Particularly, some neck and trunk muscles display multiple long regions with in-series fibers which display multiple attachments to vertebrae or ribs, each innervated by a different bundle of motor axons [Krogh and Towns, 1984;Richmond and Armstrong, 1988;Hijikata et al, 1992;Herring et al, 1993]. This arrangement may allow integration of forces exerted by multiple regions as the muscles contract.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, some neck and trunk muscles display multiple long regions with in-series fibers which display multiple attachments to vertebrae or ribs, each innervated by a different bundle of motor axons [Krogh and Towns, 1984;Richmond and Armstrong, 1988;Hijikata et al, 1992;Herring et al, 1993]. This arrangement may allow integration of forces exerted by multiple regions as the muscles contract.…”
mentioning
confidence: 99%
“…Although there is not enough information on the mechanical role of the TI for human ST muscle function, evidence from other muscles of the human body underlies the importance of compartmentalization for muscle function [Krogh and Towns, 1984;Richmond and Armstrong, 1988;Hijikata et al, 1992;Herring et al, 1993;Kamibayahsi and Richmond, 1998;Brown and McGill, 2009]. Particularly, some neck and trunk muscles display multiple long regions with in-series fibers which display multiple attachments to vertebrae or ribs, each innervated by a different bundle of motor axons [Krogh and Towns, 1984;Richmond and Armstrong, 1988;Hijikata et al, 1992;Herring et al, 1993].…”
mentioning
confidence: 99%
“…Diagrams on the right of the thoracic part, as our previous studies predicted (see Hijikata et al, 1992). The one-to-two correspondence in the fiber connection makes it impossible for a similar CSA to exist between overlapping and non-overlapping portions.…”
Section: Functional Combination Of Tapering Profiles and Overlapping mentioning
confidence: 76%
“…In terms of compartimentalization, Hijikata et al (1992) observed that in the rectus abdominis muscle of the rat, the percentage of SO fibers increases in a lateral to middle direction, whereas the opposite occurs for the frequency of FG fibers. In the rectus abdominis muscle of the tufted capuchin monkey, it was observed that both frequency and area of FG fibers increase in a proximal to distal direction, but not with a statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%